Extraction and nutritional characterization of baru almond (Dipteryx alata Vog.) water-soluble extract - SILVA, Herberth Diego Martins da; SANTOS, Fabrício Carrião dos; ANDRADE, Bruna Ribeiro Pontes de; PERFEITO, Danielle Godinho de Araújo; SIQUEIRA, Ana Paula Silva (Food Science and Technology, 2023)
This study aimed to evaluate different techniques to obtain the baru water-soluble extract and characterize the most advantageous extract in the production stage. The first part of the experiment was carried out in a factorial scheme (3 × 2) for 24 h. The almonds were used under three physical conditions: A1) raw skin; A2) toast with film; and A3) toast without film, evaluated at two absorption temperatures (25 and 80 °C). The almonds were assessed regarding the percentage of water absorption and water absorption time. After weight stabilization, the extract was obtained and evaluated. The best treatment in this productive stage, considering technological aspects, was nutritionally evaluated in macronutrients and micronutrients. The baru water-soluble extract obtained showed characteristics similar to cow’s milk in physical terms. Regarding macronutrients, about 90% of the product is water. The other 10%, in descending order of quantity, are lipids, proteins, carbohydrates, and mineral matter. The mineral composition that deserves to be highlighted in the extract is copper, iron, and zinc. Therefore, it is possible to obtain water-soluble baru extract with a good yield and good physical and nutritional aspects using roasted baru almonds without skin.